(untitled) (Journal of Parents and Teachers, 2024)
The article explores themes such as death, grief and music, featuring stories that reflect sadness and mourning. It highlights books that approach these topics from different perspectives, including optimism and humor. In addition, mention is made of the importance of music in life and its ability to connect emotionally with readers. The age recommendation for the book’s ranges from 12 to 14 years old.